If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -15 = 4x + 3 Reorder the terms: -15 + 6x = 4x + 3 Reorder the terms: -15 + 6x = 3 + 4x Solving -15 + 6x = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -15 + 6x + -4x = 3 + 4x + -4x Combine like terms: 6x + -4x = 2x -15 + 2x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 -15 + 2x = 3 + 0 -15 + 2x = 3 Add '15' to each side of the equation. -15 + 15 + 2x = 3 + 15 Combine like terms: -15 + 15 = 0 0 + 2x = 3 + 15 2x = 3 + 15 Combine like terms: 3 + 15 = 18 2x = 18 Divide each side by '2'. x = 9 Simplifying x = 9
| 4x^2-300=24 | | 100=20-5r-16 | | x*.90=1.7 | | -7(w+1)-w-8=-8(w+5)+25 | | 1+5x+25x-5=176 | | y=-2x(-1)-1 | | 7x=14/19 | | -7p-3(4-5p)=6(p-3)-6 | | 24x(2+3)= | | .13y+0.09(y+3000)=1590 | | x+68+52+x=112 | | 15=5/2x | | 2x-4y-6z=8 | | (6-17y)-(16+12y)= | | 10(v+1)-2v=2(4v+3)-11 | | 2(2+m)=2m+5 | | y+c=18whatisy | | 4x-x+4=-2 | | 4x+5=-51 | | 2+5Inx=8 | | f(x)=g(x) | | 2+51nx=8 | | 3-4x=-41 | | 1212X=13X-7 | | 4x^2+9=51-x | | 11(v+1)-3v=2(4v+3)-13 | | 36g+6=2g(6g+9) | | (7x-25)=(5x+19) | | G=(5/4)(p-91) | | 7-5(2y-1)=3y+2 | | 12y+6=62y+1 | | x=-(-w+6) |